Tricking Parents: A Review of Mechanisms and Signals of Host Manipulation by Brood-Parasitic Young - Rojas Ripari, Juan M.; Ursino, Cynthia A.; Reboreda, Juan C.; De Mársico, María C. (Frontiers in Ecology and Evolution, 2021)
Obligate avian brood parasites depend entirely on heterospecific hosts for rearing their offspring. From hatching until independence, the young parasites must deal with the challenge of obtaining sufficient parental care from foster parents that are attuned to provisioning their own offspring. Parent-offspring communication is mediated by complex begging displays in which nestlings and fledglings exhibit visual (e.g., gaping, postures) and vocal (e.g., begging calls) traits that serve as signals to parents to adjust and allocate parental effort. Parasites can manipulate host parental behavior by exploiting these stable parent-offspring communication systems in their favor. During the past 30 years, the study of host exploitation by parasitic chicks has yielded important insights into the function and evolution of manipulative signals in brood parasites. However, despite these major advances, there are still important gaps in our knowledge about how parasitic nestling and fledglings tune into the host’s communication channels and the adaptive value of the visual and acoustic signals they exhibit. Here we review the literature pertaining to host manipulation by parasitic young, focusing on four non-mutually exclusive mechanisms (i.e., host chick mimicry, begging exaggeration, host-attuned begging calls and sensory exploitation) and the function and evolution of the signals involved, with the aim to summarize and discuss putative adaptations for stimulating parental feeding and escaping host discrimination. Finally, we bring some concluding remarks and suggest directions for future research on the ways in which brood parasites adapt to the communication systems of other birds to exploit the necessary parental care.